Synthesis of partially dextran-coated gold nanoworms and anisotropic structure based dual-strategic cargo conjugation for efficient combinational cancer therapy. Issue 8 (11th January 2017) - Jang, Hongje; Kim, Young-Kwan; Min, Dal-Hee
Abstract : Partially dextran-coated gold nanoworms enabled the dual-strategic conjugation of peptides and genes. Abstract : Partially dextran-coated gold nanoworms enabled the dual-strategic conjugation of peptides and genes. Combinational cancer therapy with photothermal conversion under near-infrared irradiation was shown to be a highly efficient cancer treatment.